Harnessing Luteolin's therapeutic potential in human disorders: Medicinal significance, biological, clinical properties and analytical aspects - Abhishek Singh; Seema Yadav; Prateek Pathak; Amita Verma; Jagat Pal Yadav (Elsevier, 2024)
Introduction: Luteolin (3',4',5,7-tetrahydroxyflavone) is a common flavonoid in many fruits, vegetables, and medicinal herbs. Plants rich in luteolin have been used in Chinese traditional medicine for treating various diseases, such as hypertension, inflammatory disorders, and cancer. Throughout history, herbal medicines have been employed to address a range of health issues and their associated complications. This review delves into the biological characteristics, pharmacological importance, clinical and analytical aspects of luteolin potential use. Methods: This study explores the pharmacological properties and medicinal relevance of luteolin, drawing support from both traditional applications and scientific findings. The scientific information on luteolin has been curated from reputable sources such as Science Direct, PubMed, Google Scholar, Google, and Scopus. Additionally, this paper incorporates data from books, journals, and scientific reports to provide a well-rounded understanding of luteolin's properties. Results: Scientific investigations have underscored the biological significance and diverse medicinal potential of luteolin. Research has revealed luteolin's efficacy in exhibiting anti-inflammatory, antioxidant, anti-cancer, wound healing, antimicrobial, antiviral, and COVID-19 related properties. Furthermore, its effectiveness extends to anti-aging, antiallergic, cardioprotective, arthritis, neuroprotective, periodontal disorder, renal disorders, hepatoprotective, eye diseases, obesity, cytotoxicity, and genotoxicity. The compounds versatility as a therapeutic agent is accentuated by its adept interaction with molecular targets, influencing crucial cellular pathways. Additionally, this article provides clinical and analytical data pertaining to the identification and isolation of luteolin in various samples, underscoring its potential significance across a spectrum of health-related domains. Conclusion: The present study highlights the biological importance and therapeutic potential of luteolin, showcasing its applicability in addressing human diseases and mitigating associated side effects. Abbreviations: ADAM, A disintegrin and Metalloproteinase; AMPK, Adenosine monophosphate, Activated protein kinase; AOM, azoxymethane; AP, activator protein; ApoE, apolipoprotein E-deficient; AR, Androgen receptor; ASD, Autistic spectrum disorders; CCl4, Tetrachloromethane; ccRCC, Clear cell renal cell carcinoma; CIA, Collagen-induced arthritis; CK-MB, Creatine kinase-MB; COVID-19,Coronavirus disease 2019; COX-2, Cyclooxygenase-2; DEDD2, Death effector domain-containing protein 2; EGFR, Epidermal growth factor receptor; FZD6, Frizzled class receptor6; FZJDXJ, Fuzheng Jiedu Xiaoji formulation; GBM, Glioblastoma multiforme grade IV; H. pylori, Helicobacter pylori; HBV, Hepatitis B virus; HCC, Hepatocellular carcinoma; HGI, Hypertrophic growth factor; HIV, Human immunodeficiency virus; HNF4α, Hepatocyte nuclear factor 4α; IgE, Immunoglobulin E; IL, Interleukin; iNOS, Inducible nitric oxide synthase; IRAK1, Inhibiting interleukin-1 receptor-associated kinase; JNK, Jun N terminal kinase; K. Ras, Kirsten rat sarcoma virus; L7Gn, Luteolin-7-O-glucuronide; LDH, Lactate dehydrogenase; LIP, Labile iron pool; LPS, Lipopolysaccharide; LTL, Luteolin; MAPK, Mitogen-activated protein kinase; MDA, Malondialdehyde; MICs, Minimum inhibitory concentrations; MMP-1, Matrix metalloproteinase 1; MPTP, Mitochondrial permeability transition pores; MRSA, Methicillin-resistant staphylococcus aureus; MSH, Melanocyte-stimulating hormone; MTP, Mitochondrial transmembrane potential; NAFLD, Non-alcoholic fatty liver disease; NF, nuclear factor; NF-κB, Nuclear factor-kappa B; Nlrp3, NOD-like receptor family pyrin domain containing 3; NO, Nitric oxide; NRCMs, Neonatal rat cardiomyocytes; Nrf2, Nuclear factor erythroid 2; NSCLC, Non-small cell lung cancer; PARP, poly-ADP ribose polymerase; PC, Prostate cancer; PDEF, Prostate-derived Ets factor; PEA, Palmitoylethanolamide; PFS, Progression-free survival; POD, Post-operative delirium; PSA, Prostate-specific antigen levels; qPCR, Quantitative Polymerase chain reaction; ROS, Reactive oxygen species; Rpt, Proteasome-regulated particles; RTPCR, Real-time reverse transcriptase-polymerase chain reaction; SARS-CoV-2, Severe acute respiratory syndrome coronavirus 2; SOD, Superoxide dismutase; SREBP, Sterol regulatory element binding protein; sT antigen, Soluble tumor antigen; STAT, Signal transducer and activator of transcription; Syk, Spleen Tyrosine Kinase; TACE, Transcatheter arterial chemoembolization; TCM, Traditional chinese medicines; TNF-α, Tumor necrosis factor-α; TRAIL, TNF related apoptosis-inducing ligand; TXNIP, Thioredoxin interacting protein.